Modern Approaches to Reforms in the Economy: Performance Measurement Development in the Armed Forces of Ukraine - PAKHOLCHUK, Vadym; HORIACHEVA, Kira; TURCHENKO, Yuliia; KOVAL, Oles (Theoretical and Practical Research in Economic Fields; Vol 14 No 2 (2023): TPREF, Volume XIV, Issue 2(28), Winter 2023, 2023)
This paper reflects the empirical study of how the environment affects the performance measurement evaluation methodology in the organization, based on research of the Ukrainian Armed Forces experience. The problem is defined by the different needs of main stakeholders and management. This paper seeks the possibility to develop the role of stakeholders in performance measurement. In this research, several sources and methods were used to collect data. First, the interviews were conducted by the representatives of the research organization. Documents analysis and meetings also played a significant role in research. The paper emphasizes the influence of the environment, represented by the external actors and development vector, on the performance measurement building. Balancing between interests of stakeholders and levels of management helps to develop a performance system, which will be suitable to reflect the Armed Forces outputs and outcomes. Originality of the study of the Armed Forces of Ukraine is an extreme and interesting case because the institution is under high pressure during reforms and military conflict. But such cases facilitate the existing theory, depicting the problems and advantages of the management approaches. Future research in this area should pay more attention to the interaction between the external and internal actors in performance management methods building, especially in the defense sector .